Vascular hamartoma of the mediastinum: a case report - Güvener, Murat; Doğan, Rıza; Demircin, Metin; İlyas, Can; Paşaoğlu, İlhan (The Turkish Journal of Pediatrics, 1999)
Vascular hamartoma of the mediastinum is a rare benign vascular tumor. A 13-year-old girl presented with back pain, persistent coughing, palpitation, and angina pectoris. Preoperative investigations demonstrated an enlarging mass involving the superior mediastinum extending posteriorly (T6-T8). An encapsulated, 6x5x3 cm dark purplish mass adherent to the aortic wall was found. The main mediastinal mass was totally excised but limited resection was carried out in the paravertebral region. Microscopic examination revealed a vascular hamartoma.
Keywords: hemangioma; mediastinum; vascular hamartoma